Analysis of the Impact of Transport Corridor Vc on the Port of Ploče - Kos, Serđo; Bakota, Mario; Brčić, David (Promet - Traffic&Transportation, 2018)
The importance of the Port of Ploče lies in serving the majority of the Bosnian market. However, the Pan-European Corridor Vc provides access to a much wider market in Central and South-Eastern Europe. The purpose of this paper is to express views on the future development of the Corridor and its consequential impact on the Port. This was conducted by means of analysis, comparison, and synthesis of cargo flow data and the dynamics data of the Corridor Vc construction. It covers the relations between Bosnia and Herzegovina (BiH) and the Republic of Croatia, and the assessment of importance of the Corridor in those countries. Statistical indicators show the importance of the Corridor completion for the successful execution of port development plans. The analysis of the Corridor status points to the current prevailing circumstances in BiH that make its realization ultimately uncertain, especially its railway component. The findings show that the most significant obstacles for a successful realization of Port of Ploče development plans are not only within the BiH internal geo-political relationships but in the disputes between BiH and the Republic of Croatia (RH) as well. Consequently, it has been shown that the Port of Ploče is not able to define and carry out the necessary measures toward BiH on its own but necessarily with the participation of the RH Government. The analysis offers observations and recommendations for improving relations with BiH, which would significantly advance the completion of the Corridor in BiH. In this way, it would allow for a full establishment of the Port of Ploče on target markets.